CAPABILITY OF LEMIGAS LABORATORIES IN SUPORTING EOR STUDIES* - Rachmat Sudibjo; Herlan Adim (Scientific Contributions Oil and Gas, 1992)
Eor methods hold the promise of adding to the production levels and reserve base of world’s maturing oil fields. In Indonesia, very few EOR project have been under taken, only few of the EOR methods that have been evaluated in the laboratory and tested in the field.